2018
DOI: 10.1007/s10461-018-2055-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Illness, Substance Use, and Viral Suppression Among HIV-Positive Men of Color Who Have Sex with Men in Los Angeles

Abstract: For individuals living with human immunodeficiency virus (HIV), viral suppression positively affects quality and length of life and reduces risks for HIV transmission. Men of color who have sex with men (MoCSM) who have been diagnosed with HIV have disproportionately low rates of viral suppression, with concomitant increases in incidence. We identified specific social, structural, and psychiatric factors associated with viral suppression among a sample of 155 HIV-positive MoCSM. Cigarette smoking and biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 40 publications
(48 reference statements)
0
22
0
Order By: Relevance
“…The methodology of our ongoing prospective cohort study (‘mSTUDY’) has been described in detail elsewhere . Briefly, it is a National Institute of Drug Abuse‐funded program with the overall objective of measuring factors linking substance use with dynamics of HIV transmission and progression (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology of our ongoing prospective cohort study (‘mSTUDY’) has been described in detail elsewhere . Briefly, it is a National Institute of Drug Abuse‐funded program with the overall objective of measuring factors linking substance use with dynamics of HIV transmission and progression (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Mainland-US-born Hispanics/Latinos were more likely than PR-born and non-US-born Hispanics/Latinos to report the use of drugs and were more likely than non-US-born Hispanics/Latinos to report symptoms of anxiety and depression. Psychiatric illnesses combined with substance use are associated with poor HIV outcomes [22,23]. Persons with diagnosed HIV who are using drugs are less likely to adhere to treatment and achieve viral suppression [22], and those who are experiencing current symptoms of depression combined with the use of cocaine or methamphetamine were found to have lower odds of virologic suppression [23].…”
Section: Discussionmentioning
confidence: 99%
“…These populations have consistently higher smoking rates than the general population, 1 have several shared vulnerabilities, 2 and are often more refractory to treatment. 3 Continued smoking has important negative impacts on treatment of their primary disease and their prognosis for recovery, 4 and special care is often needed for successful tobacco dependence treatment. 5 These ''forgotten groups'' continue to smoke in significant numbers and experience significant health disparities because they have not been receiving the needed protection from tobacco control policies.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking has been associated with poor medication adherence and prognosis among PLWHA, 16 and a study found that medication adherence was negatively influenced by smoking in an HIV-positive sample of men of color who have sex with men. 4 The authors of this study point out that smoking prevention and treatment is one of the most important interventions that can be provided to PLWHA, especially among minorities. Smoking may also complicate treatment of many mental health disorders by reducing blood levels of neuroleptics, such as olanzapine, clozapine, haloperidol, chlorpromazine, and fluphenazine, 17 making it likely that smokers will require higher doses to achieve a therapeutic effect, which exposes them to an increased risk of side effects from psychotherapeutic medications.…”
Section: Introductionmentioning
confidence: 99%